Evolutionary game analysis of supply chain financing for film and television enterprises considering co-production - Ye Zhen; Hui Li; Wenli Wang (PLoS ONE, 2025)
Currently, many film and television enterprises struggle with insufficient funds during the visualization process. To address this issue, companies can opt to enter into co-production agreements with sales platforms, implement supply chain financing, obtain financing through banks, or collaborate with all three parties simultaneously. The paper presents a tripartite evolutionary game model involving film and television enterprises, sales platforms, and banks and discusses the strategic choices of operation and the investment and financing behaviors of the three parties. Additionally, it analyzes film and television enterprises’ capital, film production costs, copyright acquisition costs, and other factors and examines the impact of these factors on their strategic choices. The study shows that only when film and television enterprises have strong negotiation abilities will a sales platform consider establishing a cooperative relationship with them. As the cost of film production increases, the requirement for the negotiation ability of film and television companies also increases accordingly. Once the cooperation of the sales platform is obtained, film and television enterprises can actively complete the film shooting. If the sales platform chooses not to cooperate, the film and television enterprises’ capital will be restricted. In the case of non-cooperation, if the film production cost is low, enterprises can still choose to complete the film using bank financing. In contrast, even if they have obtained the support of bank loans, the high production cost of the film compels the film and television enterprises to adopt the strategy of negative completion. The research provides theoretical support for further alleviating the financing difficulties of film and television enterprises and at the same time provides a theoretical basis for the cooperation among film and television enterprises, sales platforms, and banks.